Use f(x) = 5x − 2 and g(x) = 4 − x2 to evaluate the expression. (a) (f c

Algebra
Tutor: None Selected Time limit: 1 Day

Use 

f(x) = 5x − 2
 and 
g(x) = 4 − x2
 to evaluate the expression.
(a)    
(f  g)(x)
 
 

(b)    
(g  f)(x)
 
 
Jun 30th, 2015

Hi !

f(x) = 5x - 2

g(x) = 4 - x^2

(a)

(fog)(x) = 5(4 - x^2) - 2

             = 20 - 5x^2 - 2

             = - 5x^2 + 18

(b)

(gof)(x) = 4 - (5x - 2)^2

             = 4 - (25x^2 + 4 - 20x)

             = 4 - 25x^2 - 4 + 20x

             = - 25x^2 + 20x

             = - 5x(5x - 4)

Hope you get it. Thanks :)
Jun 30th, 2015

my program is saying this is an exact answer

Jun 30th, 2015

Answer is not right?

Jun 30th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 30th, 2015
...
Jun 30th, 2015
May 26th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer